Exploratory Analysis in the Differences in Blood Serum and Seminal Plasma of Adipose-Tissue Related Peptides in Obese and Non-Obese Men and Their Correlations With Semen Parameters - Antinozzi, Cristina; Lista, Marco; Caponecchia, Luisa; Salacone, Pietro; Minganti, Carlo; Battaglia, Francesco A.; Di Luigi, Luigi; Sgrò, Paolo (Frontiers in Endocrinology, 2021)
Objectives: Evaluating the relationship between circulating metabolic biomarkers. and semen parameters in obese, overweight and normal-weight patients. Methods: Patients were recruited at the “Andrology and Pathophysiology of Reproduction Unit”, in Santa Maria Goretti Hospital. 98 participants were divided into three groups (obese, overweight and normal-weight patients) according to BMI and were analyzed for three adipokines and six hormone peptides in blood serum and seminal plasma using Luminex assay. Standard semen analysis was performed for ejaculate volume, sperm concentration, total sperm count, motility, morphology and leukocytes. Results: In all groups of subjects, we observed a higher concentration of blood serum c-peptide, GIP, PAI-1, leptin, ghrelin and GLP-1 in comparison to seminal plasma; differently, higher levels in seminal plasma were observed for insulin and visfatin. In comparison to the non-obese subjects, obese subjects showed a higher blood serum concentration of c-peptide, GLP-1, GIP and leptin and a higher concentration of seminal plasma of GIP and insulin. Total sperm count, progressive motility, motility, and atypical forms directly correlated with PAI-1 and visfatin, whereas GLP-1 directly correlated only with total progressive motility. Conclusion: Obese men showed a different pattern of blood serum and seminal plasma adipokines and hormone peptides concentrations in comparison to normal-weight men. Furthermore, these molecules correlated with functional seminal parameters. Our findings support the option to consider these molecules as new biomarkers and pharmacological targets for a new therapeutic approach in male infertility. However, further studies identifying other potential biomarkers of male infertility with important clinical implication and characterizing their mechanisms of action are mandatory.